Screening for developmental delay in urban Rwandan children: a cross sectional study - Victoire Tuyisenge; Febronie Mushimiyimana; Aimable Kanyamuhunga; Jean Paul Rukabyarwema; Archana A. Patel; Cliff O'Callahan (BMC, 2023)
Abstract Background Systematic or targeted screening for developmental delay (DD) is critical to the early identification of developmental disabilities. With limited available information for urban Rwandan children, this study aimed to determine the prevalence of DD and associated risk factors in infants aged 9 to 16 months living in the urban Rwandan city of Kigali. Methods A cross-sectional study was conducted in Rwanda from August to November 2019. A convenience sample of 376 Rwandan parents/caregivers and their children attending urban health centers for their routine immunization visits at 9 and 15 months of age was studied. Parents/caregivers completed the official Kinyarwandan version of the Ages and Stages Questionnaire (ASQ-3) and established cutoffs were used to identify DD. Frequency and percentages were used to summarise the data. Logistic regression analysis was used to identify factors associated with DD. Results Of the 358 children screened using the ASQ-3, the overall prevalence of DD was 24.6%, with a 27.2% prevalence among 9-10-month old children and 22.4% prevalence among 15-16-month old children. Delays in the combined group among the domains of gross motor, communication, fine motor, personal social, and problem solving were 12.8%, 2.5%, 8.4%, 1.7% and 7.5%, respectively. Gestational age at delivery and district of origin were most highly associated with DD, with preterm children at significantly higher risk of having DD compared to term children (Adjusted Odd Ratio AOR = 8.3; 95% CI = 2.5-27.4) and children from Nyarugenge District at high risk of DD compared to children from Gasabo district (AOR = 2.15; 95% CI = 1.2-3.9). Conclusions The prevalence of ASQ-detectable DD among urban Rwandan children between 9 and 16 months of age was 24.6%, with a high correlation to a history of prematurity and district of origin. This study demonstrates the need for thoughtful health planning regarding integrated developmental surveillance for children, particularly those at high risk, to allow for earlier identification and intervention in the urban area of Kigali, Rwanda.